2020
DOI: 10.3390/nano10040726
|View full text |Cite
|
Sign up to set email alerts
|

Double Metal Oxide Electron Transport Layers for Colloidal Quantum Dot Light-Emitting Diodes

Abstract: The performance of colloidal quantum dot light-emitting diodes (QD-LEDs) have been rapidly improved since metal oxide semiconductors were adopted for an electron transport layer (ETL). Among metal oxide semiconductors, zinc oxide (ZnO) has been the most generally employed for the ETL because of its excellent electron transport and injection properties. However, the ZnO ETL often yields charge imbalance in QD-LEDs, which results in undesirable device performance. Here, to address this issue, we introduce double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…The low-binding-energy cutoff (around 4.0 eV) is relevant to the energy difference between the valence band (VB) and the E F ; therefore, the VB values of the ZnO NC films without and with PFN-Br, PFN-BF 4 , and PFN-PF 6 modification were calculated to be −7.49, −7.41, −7.52, and −7.47 eV, respectively. The obtained VB values of ZnO NC films in this study are close to the reported values in the literature. , To lead out the conduction band (CB), the energy bandgap ( E g ) of ZnO NCs without and with CPEs should be acquired first. Figure S6a shows the absorption spectra of the original and CPE-modified ZnO NC films, and the E g of ZnO NCs is estimated from the Tauc plot in Figure S6b to be 3.23 eV.…”
Section: Resultssupporting
confidence: 86%
“…The low-binding-energy cutoff (around 4.0 eV) is relevant to the energy difference between the valence band (VB) and the E F ; therefore, the VB values of the ZnO NC films without and with PFN-Br, PFN-BF 4 , and PFN-PF 6 modification were calculated to be −7.49, −7.41, −7.52, and −7.47 eV, respectively. The obtained VB values of ZnO NC films in this study are close to the reported values in the literature. , To lead out the conduction band (CB), the energy bandgap ( E g ) of ZnO NCs without and with CPEs should be acquired first. Figure S6a shows the absorption spectra of the original and CPE-modified ZnO NC films, and the E g of ZnO NCs is estimated from the Tauc plot in Figure S6b to be 3.23 eV.…”
Section: Resultssupporting
confidence: 86%
“…The degradation of the efficiency compared with the normal devices is attributed to the current crowding effect and efficiency roll-off at high current density. (25)(26)(27)(28) The leakage originates from structure variation also plays a part. The localized current density will also aggravate the Auger recombination.…”
Section: Resultsmentioning
confidence: 99%
“…In order to achieve a commercially feasible QD–LED, many studies were performed to understand the mechanisms regarding the interaction between QDs and charge transport layers [ 6 , 7 , 8 ]. During the operation of QD–LEDs, the QD active layer is generally affected by a complex combination of electric field effects and carrier charging across the device, leading to different quenching mechanisms, such as the field induced quenching, [ 9 , 10 ], interfacial charge transport [ 11 ], and charged QDs by excess charge injection [ 12 ].…”
Section: Introductionmentioning
confidence: 99%